Becoming a Movement: Early Nineteenth-Century Hasidism in the Eyes of R. Kalonymus Kalman Epstein of Kraków. - Gellman, Uriel (Modern Judaism: A Journal of Jewish Ideas & Experience, 2018)
The article explores the transformation of Hasidism from a marginal, elitist group into a modern socio-religious mass movement in Eastern Europe in the nineteenth century from the perspective of rabbi R. Kalonymus Kalman Epstein. It provides a background of the life of R. Kalman which covers his exposure to Hasidism in Kraków, Poland at an early age. Information is also presented on the expansion of Hasidism through Eastern Europe.